2012
DOI: 10.1002/jcp.23014
|View full text |Cite
|
Sign up to set email alerts
|

Role of ecto‐NTPDases on UDP‐sensitive P2Y6 receptor activation during osteogenic differentiation of primary bone marrow stromal cells from postmenopausal women

Abstract: This study aimed at investigating the expression and function of uracil nucleotide-sensitive receptors (P2Y(2), P2Y(4), and P2Y(6)) on osteogenic differentiation of human bone marrow stromal cells (BMSCs) in culture. Bone marrow specimens were obtained from postmenopausal female patients (68 ± 5 years old, n = 18) undergoing total hip arthroplasty. UTP and UDP (100 µM) facilitated osteogenic differentiation of the cells measured as increases in alkaline phosphatase (ALP) activity, without affecting cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(119 citation statements)
references
References 73 publications
4
94
0
Order By: Relevance
“…Recently, extracellular nucleotides have been reported to modulate the differentiation of human MSCs, with the P2X6, P2Y 4 and P2Y 14 receptors identified as playing pivotal roles in this process [292,293]. UDP activation of P2Y 6 receptors has also been shown to regulate the osteogenic differentiation of the primary MSCs from postmenopausal women [291]. The same study also demonstrated that NTPDases influence which osteoblast progenitors are driven into proliferation or differentiation [291].…”
Section: Bone Marrow Stromal Cells or Mesenchymal Stem Cellsmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, extracellular nucleotides have been reported to modulate the differentiation of human MSCs, with the P2X6, P2Y 4 and P2Y 14 receptors identified as playing pivotal roles in this process [292,293]. UDP activation of P2Y 6 receptors has also been shown to regulate the osteogenic differentiation of the primary MSCs from postmenopausal women [291]. The same study also demonstrated that NTPDases influence which osteoblast progenitors are driven into proliferation or differentiation [291].…”
Section: Bone Marrow Stromal Cells or Mesenchymal Stem Cellsmentioning
confidence: 92%
“…UDP activation of P2Y 6 receptors has also been shown to regulate the osteogenic differentiation of the primary MSCs from postmenopausal women [291]. The same study also demonstrated that NTPDases influence which osteoblast progenitors are driven into proliferation or differentiation [291]. Furthermore, a detailed investigation using knockout mice identified that the P2Y 13 receptor regulates the terminal differentiation of MSCs into osteoblasts or adipocytes [207].…”
Section: Bone Marrow Stromal Cells or Mesenchymal Stem Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…Data are means ± SEM (n = 3 independent preparations) compared to Wnt3a alone for up to 24 h post-treatment. As nucleotides are rapidly degraded once released into the extracellular milieu [32,33], it is likely that the prolonged potentiation of canonical Wnt signaling is due at least in part to changes in expression of secondary factors or pathway components. One possibility is that activation of P2X7 receptors leads to alterations in the expression of Wnt pathway components.…”
Section: P2x7 Potentiates the Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…Adipose tissue-derived stem cells (ATSCs) and dental follicle cells (DFCs) derived from the ectomesenchyme expressed some P2X (P2X 3,4,5,6,7 ) and all 8 P2Y receptor subtypes; interestingly, no mRNA transcripts of P2X 1 and P2X 2 receptors were identified in either cell type [90,91]. Extracellular nucleotides acting through P2 receptors (primarily P2X 6 , P2Y 4 , P2Y 6 , P2Y 13 and P2Y 14 ) are important modulators of MSC differentiation towards the osteogenic and adipogenic lineages [90][91][92]. The purinergic concept of MSC differentiation is further supported by a recent study showing substantial changes in ecto-nucleotide metabolism and ecto-nucleotidase expression profiles following chondrogenic differentiation of human umbilical cord-derived MSCs [93].…”
Section: P2 Purinergic Receptor Expression and Function During Chondrmentioning
confidence: 99%